Application and Evaluation of Global Geoid Models for Orthometric Height Determination in Al-Kufra Region, Libya (Al-Farooq Journal of Sciences, 2026)
Determining the geoid undulation (N) is essential for converting geodetic (ellipsoidal) heights obtained from Global Positioning System (GPS) receivers into orthometric heights, which are required in most engineering and surveying applications. Because global geoid models do not provide uniform accuracy across all regions of the Earth, local evaluation of these models prior to their adoption is essential. This study aims to apply and evaluate the accuracy of five global geoid models — EGM2008-5, EGM96-5, EGM96-15, EGM84-15 and EGM84-30 — in the Al-Kufra region in southeastern Libya, in order to identify the most accurate model for computing geoid undulation. The study relied on ten points with known geographic coordinates and ellipsoidal heights. The geoid undulation value at each point was extracted from each model using the Geoid Height Calculator tool, and the resulting orthometric heights were compared with reference orthometric heights obtained from spirit-levelling work. A statistical analysis comprising the arithmetic mean and standard deviation was performed for each model. The results showed that the EGM2008-5 model was the most accurate among the five, with the lowest standard deviation of 0.130 m, followed by EGM96-5 and EGM96-15 with a standard deviation of about 0.18 m, while EGM84-15 and EGM84-30 showed the lowest accuracy, with a standard deviation exceeding 0.38 m. The study recommends adopting EGM2008-5 for surveying work in the Al-Kufra region, while expanding the study to other regions of Libya and increasing the number of observation points to strengthen the reliability of the results.
Keywords: Geoid; Global Geoid Models; EGM2008; Orthometric Height; Geodetic Height; Global Positioning System (GPS); Geoid Undulation; Standard Deviation; Al-Kufra Region.